2020
DOI: 10.1111/os.12591
|View full text |Cite
|
Sign up to set email alerts
|

Blood Metal Ion Release After Primary Total Knee Arthroplasty: A Prospective Study

Abstract: Objectives:To investigate the course of in vivo blood metal ion levels in patients undergoing primary total knee arthroplasty (TKA) and to investigate potential risk factors associated with metal ion release in these patients. Methods:Twenty-five patients with indication for TKA were included in this prospective study. Whole blood metal ion analysis was performed pre-operatively and at 1 week, 6 weeks, 3 months, 6 months, and 12 months postoperatively. Clinical scores were obtained using the American Knee Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…In TKA, wear-related problems have typically been reported in terms of damage to the PE insert. 5 although retrieval studies have recently demonstrated that abrasive and corrosive damage commonly occurs at the femoral component of tKas, little is known about metal ion exposure in patients with well-functioning TKAs. 21 no limit values for serum metal ion concentrations have been established for TKA, but ion concentrations above 2 μg/l are considered to be a potentially critical value for mom hip arthroplasty according to current guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In TKA, wear-related problems have typically been reported in terms of damage to the PE insert. 5 although retrieval studies have recently demonstrated that abrasive and corrosive damage commonly occurs at the femoral component of tKas, little is known about metal ion exposure in patients with well-functioning TKAs. 21 no limit values for serum metal ion concentrations have been established for TKA, but ion concentrations above 2 μg/l are considered to be a potentially critical value for mom hip arthroplasty according to current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, few data have been published regarding metal ion concentrations following tKa, as metal ion concentrations seldom exceed 1 μg/l in primary TKA. 5 due to the constrained hinge mechanism and the resulting mechanical forces on the coupling, recent studies have shown increased serum levels of cobalt and chromium in the majority of patients receiving mom hinged knee designs combined with a modular revision knee system for the treatment of very large bone defects. [6][7][8] The implants examined in these studies were mostly modular tumour-or megaprostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Nach 5 Jahren zeigten jedoch alle Patienten unabhängig von der Beschichtung wieder Werte für Chrom von unter 2 μg/l. Für Kobalt, welches die Haupt- [15,33,36] und andere Arbeiten, die die Metallionenfreisetzung bei der Verwendung von Knieimplantaten untersucht haben, berichten über erhöhte Werte für Chrom und Kobalt bis zu 10 Jahre nach Implantation [7,17,27]. Für Nickel, das Metall, welches am häufigsten Hautallergien hervorruft (bis zu 20,1 % [28]) und daher in den Patientengesprächen oft benannt wird, wurden keine Änderungen der Konzentration bis zu 5 Jahre nach Operation in beiden Patientengruppen gemessen.…”
Section: Metallionenkonzentrationunclassified
“…The 10-year survival ratio of TKA is approximately 90 % (1). One of the major causes for revision is aseptic loosening, caused by wear debris, mainly polyethylene (1)(2)(3)(4). Wear debris is generated by biotribocorrosion, a process induced by mechanical No benefits or funds were received in support of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Acta Orthopaedica Belgica, Vol. 87 -4 -2021 wear, which ruptures the passive film formed on the prosthesis surface and thus leaves the metallic surface exposed to corrosive media (2,5). However, the effects of metal wear debris (metal particles and ions), which is around 1/10 th of the total wear debris, have been underestimated.…”
Section: Introductionmentioning
confidence: 99%